On solving nonconvex optimal control problems with a terminal objective functional - Strekalovsky, A.S.; Yanulevich, M.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
A nonconvex optimal control problem for a linear-in-state system of ordinary differential equations with a terminal objective functional given by the difference of two convex functions is considered. New local and global search algorithms are tested. A special generating method of linear-quadratic test optimal control problems is developed. The testing results confirm the efficiency of the proposed algorithms.